Olefin cross metathesis based de novo synthesis of a partially protected L-amicetose and a fully protected L-cinerulose derivative - Schmidt, Bernd; Hauke, Sylvia (Beilstein Journal of Organic Chemistry, 2014)
Cross metathesis of a lactate derived allylic alcohol and acrolein is the entry point to a de novo synthesis of 4-benzoate protected L-amicetose and a cinerulose derivative protected at C5 and C1.
Keywords: carbohydrates; de novo synthesis; lactate; metathesis; ruthenium